The Sick Role: A Contemporary Analysis of Women, Alcoholism, and Gender Ideology. Issue 1 (2nd January 2018) - Sanders, Jolene
ABSTRACT: This qualitative study analyzes gender role ideology and how it shapes the process of addiction and pathways to recovery for women in Alcoholics Anonymous (AA). More than 600 women's stories submitted to The Grapevine: The International Journal of Alcoholics Anonymous between the late 1940s and through the 1980s provides the sample from which dominant themes are extrapolated. The sick role as conceptualized by Talcott Parsons in the 1950s is tested, and it is found that sex roles (now discussed as gender roles) do influence and shape women's experiences as alcoholics and their pathways to recovery. The double standard is identified early on whereas more public displays of deviance are not widely discussed until the 1980s. In between, the labeling of women with "bad nerves, " the overuse of sedatives, and the struggle to accept the disease model of alcoholism are all discussed in these women's stories.